Knowledge markets: a typology and an overview. (2016) - Carrillo, Francisco Javier
Knowledge markets are defined as value exchange systems where the quantity, quality and terms of interactions amongst agents are determined primordially by the dynamic properties of intellectual capital creation and exchange. Such properties include the attributes of knowledge-based value production as well as a distinctive ethos and organisational design. Based on this definition, an array of ten types of knowledge markets is introduced, with a synthetic characterisation for each category. First level types are: intellectual capital dealing, open dealing, crowd dealing, cooperative dealing, non-monetary dealing, social dealing, alternative currencies plus incentive regimes, alternative banking, open knowledge labs and emerging knowledge markets. Each category is broken down into subtypes, each subtype in turn characterised and/or exemplified. The typology description is accompanied by an extensive and updated literature review. The resulting map of knowledge markets may contribute to understand the uniqueness of these novel value-generation arrangements and capitalise on their transformative power.